Light Intensity Pattern Under Agroforestry System - Jha, M. N.; Gupta, M. K. (Indian Forester, 2003)
A study was conducted in Saini Majra (Haryana) under agroforestry system and at nearby open area to investigate the light intensity pattern under both the sites. Open area received 96.42% higher light intensity as compared to agroforestry system because there were no trees on the field. Maximum light intensity was recorded during mid-day (1210 to 1235 hrs) under both the sites. It is evident from the study that Poplar trees planted in agroforestry system can absorb or reflect up to 51.76% solar radiation before reaching to the ground even at a leafless stage.